Nursing students' knowledge and compliance with standard precautions. - Lopes, Maria de Lourdes; Lima, Tallyne da Silva; Oliveira, Adélia Dalva da Silva; Amorim, Fernanda Cláudia Miranda; Sousa, Kayo Henrique Jardel Feitosa; Figueiró, Rachel Ferreira Savary; Zeitoune, Regina Célia Gollner; Damasceno, Carolinne Kilcia Carvalho Sena (Acta Paulista de Enfermagem, 2023)
Objective: To describe nursing students' knowledge and compliance with standard precautions. Methods: This is a descriptive and quantitative study with 161 nursing students. Data were collected between September and October 2020, through an electronic form and processed in the Statistical Package for the Social Sciences program, through descriptive analyses. Results: The mean scores of knowledge and compliance with standard precautions showed satisfactory levels, i.e., higher than half of the possible score. Students recognized that these measures extend beyond care for patients diagnosed with infection or who are in the incubation period of the infectious process. However, they limit their objective to the health team protection, neglecting patient protection. Hand hygiene, as well as the use of gloves in procedures involving contact with potentially contaminated biological material, was the most adopted measure by students. It was observed that compliance with protective measures is higher in the final periods of graduation. Conclusion: We identified weaknesses in students' knowledge regarding the basic notions that guide and support the adoption of security measures. It is essential to have a nursing curriculum that, throughout the academic cycles, continuously incorporates the prevention and control of infections related to health care in its scope of discussions. This care will be reflected not only in the quality of the care provided, but also in the maintenance of students' health – future workers in the area.